ANALISIS NORMATIF-FILOSOFIS FATWA DEWAN SYARI’AH NASIONAL MAJELIS ULAMA’ INDONESIA (DSN-MUI) TENTANG TRANSAKSI JUAL BELI PADA BANK SYARI’AH - Fathoni, Nur (Al-Ahkam, 2015)
DSN-MUI uses trade transactions in Islamic financial institutions in order to avoid interest rate system. Moral and legal issues had became the important thing in the formulation of trade transaction in syariah banking, since the concern about the system of interest that still exist in syariah bankingâ€™s trade transaction. This means that the trade transaction on syariah banking according to fatwa DSN-MUI still contains usury (riba). This paper intends to explore the important things about theÂ  rules and practices of trade transaction on the syariah banking according to DSN-MUI. This study concluded that DSN-MUI performs ijtihÄd taá¹bÄ«qÄ« to facilitate the concept of trade operations on syariah banking. DSN-MUIâ€™s fatwa about trade transaction appears to correspond to a normative concept of fiqh. It's just that there is ambiguity in the salam and istithnÄ' contract and less attention to the philosophy of trade. The trade transactions were reduced as provision of funds for purchasing of goods, with multi contract institutions. The use of supporting contracts that are not true will potentially lead to morality inconsistencies in trade transactions.